2018
DOI: 10.1007/s11060-018-2908-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular classification of patients with grade II/III glioma using quantitative MRI characteristics

Abstract: Quantitative imaging characteristics of FLAIR heterogeneity and border pattern in grade II/III gliomas may provide unique information for determining molecular status at time of initial diagnostic imaging, which may then guide subsequent surgical and medical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 51 publications
(75 reference statements)
1
17
0
Order By: Relevance
“…8 Similar results were observed by Bahrami et al, who defined their findings quantitatively as edge contrast (EC). 1 The authors also observed that IDH-wild type tumors had higher T2-signal heterogeneity than IDH-mutant tumors, while the presence of a 1p/19q codeletion was associated with higher signal het-erogeneity among the latter. Diffusion-and perfusionweighted imaging have also been suggested to be effective methods for classifying LGGs on the basis of molecular status.…”
Section: Discussionmentioning
confidence: 92%
“…8 Similar results were observed by Bahrami et al, who defined their findings quantitatively as edge contrast (EC). 1 The authors also observed that IDH-wild type tumors had higher T2-signal heterogeneity than IDH-mutant tumors, while the presence of a 1p/19q codeletion was associated with higher signal het-erogeneity among the latter. Diffusion-and perfusionweighted imaging have also been suggested to be effective methods for classifying LGGs on the basis of molecular status.…”
Section: Discussionmentioning
confidence: 92%
“…TA using B 0 and fractional anisotropy maps has also shown a high accuracy of 95% in predicting IDH status. 50 Bahrami et al 51 reported greater FLAIR tissue heterogeneity and lower edge contrast in IDH wild-type compared with IDH mutants. Jakola et al 53 also reported greater accuracy for predicting IDH mutation using 3D-FLAIR.…”
Section: Glioma Radiogenomicsmentioning
confidence: 99%
“…And the texture analysis based on T2 FLAIR images has been demonstrated to be helpful and accurate in predicting IDH mutation [30,31]. T2 FLAIR features also showed distinct characteristics between IDH wildtype and mutant tumors,1p/19q co-deleted and 1p/19q intact tumors, MGMT methylated and unmethylated tumors respectively, which could useful in molecular classification of patients with grade II/III glioma [32]. In addition, T2 FLAIR is increasingly involved in the texture analysis for assessment of therapeutic response and survival outcomes.…”
Section: Introductionmentioning
confidence: 97%